(untitled) (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
The Covid-19 pandemic that occurred in March 2020 had an impact on all aspects of the country, including Indonesia, not only impacting health cases but also impacting economic cases. In the economic aspect it influences people’s lives. By providing motivation and building an entrepreneurial spirit, of course, we can provide solutions to the problems faced so that we can increase awareness and continue to be creative so that we can play an active role in improving the economy. The target of this community service activity is the residents of Trukan Segoroyoso, Pleret, Bantul, Yogyakarta. The purpose of this community service is that it is hoped that participants can add entrepreneurial insight and get an overview of businesses that can improve the economy in a pandemic situation. The method for carrying out this activity is in the form of lectures and discussions about Growing an Entrepreneurial Spirit During the Covid-19 Pandemic at the Trukan Segoroyoso Pleret Padukuhan, Bantul, Yogyakarta. Keywords:Entrepreneurship, Motivation, Businesses